Dual-filament regulation of relaxation in mammalian fast skeletal muscle - Cameron Hill; Michaeljohn Kalakoutis; Alice Arcidiacono; Flair Paradine Cullup; Yanhong Wang; Atsuki Fukutani; Theyencheri Narayanan; Elisabetta Brunello; Luca Fusi; Malcolm Irving (Proceedings of the National Academy of Sciences, 2025)
Muscle contraction is driven by myosin motors from the thick filaments pulling on the actin-containing thin filaments of the sarcomere, and it is regulated by structural changes in both filaments. Thin filaments are activated by an increase in intracellular calcium concentration [Ca 2+ ] i and by myosin binding to actin. Thick filaments are activated by direct sensing of the filament load. However, these mechanisms cannot explain muscle relaxation when [Ca 2+ ] i decreases at high load and myosin motors are attached to actin. There is, therefore, a fundamental gap in our understanding of muscle relaxation, despite its importance for muscle function in vivo, for example, for rapid eye movements or, on slower timescales, for the efficient control of posture. Here, we used time-resolved small-angle X-ray diffraction (SAXD) to determine how muscle thin and thick filaments switch OFF in extensor digitorum longus (EDL) muscles of the mouse in response to decreases in either [Ca 2+ ] i or muscle load and to describe the distribution of muscle sarcomere lengths (SLs) during relaxation. We show that reducing load at high [Ca 2+ ] i is more effective in switching OFF both the thick and thin filaments than reducing [Ca 2+ ] i at high load in normal relaxation. In the latter case, the thick filaments initially remain fully ON, although the number of myosin motors bound to actin decreases and the force per attached motor increases. That initial slow phase of relaxation is abruptly terminated by yielding of one population of sarcomeres, triggering a redistribution of SLs that leads to the rapid completion of mechanical relaxation.